Microbial Processes and Microbial Communities in the Water Column of the Polar Meromictic Lake Bol’shie Khruslomeny at the White Sea Coast - Savvichev, Alexander S.; Kadnikov, Vitaly V.; Rusanov, Igor I.; Beletsky, Alexey V.; Krasnova, Elena D.; Voronov, Dmitry A.; Kallistova, Anna Yu.; Veslopolova, Elena F.; Zakharova, Elena E.; Kokryatskaya, Nataliya M.; Losyuk, Galina N.; Demidenko, Nikolai A.; et al. (Frontiers in Microbiology, 2020)
Microbiological, molecular ecological, biogeochemical, and isotope geochemical research was carried out at the polar Lake Bol'shie Khruslomeny at the coast of the Kandalaksha Bay, White Sea in Marc and September 2017. The uppermost mixolimnion was oxic, with low salinity (3–5‰). The lower chemocline layer was brown-green colored, with very high content of particulate organic matter (up to 11.8 mg C L-1). The lowermost monimolimnion had marine salinity (22–24‰) and very high concentrations of sulfide (up to 18 mmol L-1) and CH4 (up to 1.8 mmol L-1). In the chemocline, total microbial abundance and the rate of anoxygenic photosynthesis were 8.8 · 106 cells mL-1 and 34.4 µmol C L-1 day-1, respectively. Both in March and September, sulfate reduction rate increased with depth, peaking (up to 0.6−1.1 µmol S L-1 day-1) in the lower chemocline. Methane oxidation rates in the chemocline were up to 85 and 180 nmol CH4 L-1 day-1 in March and September, respectively; stimulteion of this process by light was observed in September. The shares of cyanobacteria and methanotrophs in the layer where light-induced methane oxidation occurred were similar, ~2.5% of the microbial community. Light did not stimulate methane oxidation in deeper layers. The carbon isotope composition of particulate organic matter (δ13C-Corg), dissolved carbonates (δ13C-DIC), and methane (δ13C- СН4) indicated high microbial activity in the chemocline. Analysis of the 16S rRNA gene sequences revealed predominance of Cyanobium cyanobacteria (order Synechococcales) in the mixolimnion. Green sulfur bacteria Chlorobium phaeovibrioides capable of anoxygenic photosynthesis constituted ~20% of the chemocline community both in March and in September. Methyloprofundus gammaptoteobacteria (family Methylomonaceae) were present in the upper chemocline, where active methane oxidation occurred. During winter, cyanobacteria were less abundant in the chemocline, while methanotrophs occurred in higher horizons, including the under-ice layer. Chemolithotrophic gammaproteobacteria of the genus Thiomicrorhabdus, oxidizing reduced sulfur compounds at low oxygen concentrations, were revealed in the chemocline in March. Both in March and September archaea constituted up to 50% of all microorganisms in the hypolimnion. The share of putative methanogens in the archaeal community was low, and they occurred mainly in near-bottom horizons.